2014
DOI: 10.1111/cge.12505
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of BRCA1 and BRCA2 mutations in unselected breast cancer patients from Peru

Abstract: The prevalence of BRCA1 and BRCA2 mutations among breast cancer patients in Peru has not yet been explored. We enrolled 266 women with breast cancer from a National cancer hospital in Lima, Peru, unselected for age or family history. DNA was screened with a panel of 114 recurrent Hispanic BRCA mutations (HISPANEL). Among the 266 cases, thirteen deleterious mutations were identified (eleven in BRCA1 and two in BRCA2), representing 5% of the total. The average age of breast cancer in the mutation-positive cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 31 publications
2
45
0
Order By: Relevance
“…A 2008 study demonstrated that seven Brazilian 5382insC carriers all shared the same haplotype [38]. Interestingly, this mutation was not observed in the other Latin American HISPANEL studies [10,11,20,27] and despite the significant difference in colonization patterns in Latin America countries (Brazil was mainly colonized by Portugal, while other Latin American countries were mainly colonized by Spain), there is no description of this mutation among Portuguese HBOC families, and only one Spanish carrier was reported [39].…”
Section: Resultsmentioning
confidence: 99%
“…A 2008 study demonstrated that seven Brazilian 5382insC carriers all shared the same haplotype [38]. Interestingly, this mutation was not observed in the other Latin American HISPANEL studies [10,11,20,27] and despite the significant difference in colonization patterns in Latin America countries (Brazil was mainly colonized by Portugal, while other Latin American countries were mainly colonized by Spain), there is no description of this mutation among Portuguese HBOC families, and only one Spanish carrier was reported [39].…”
Section: Resultsmentioning
confidence: 99%
“…Reports from other South-American countries also find similar prevalence of BRCA mutations but smaller rates of recurrent mutations [45,50]. Solano et al evaluated BRCA gene sequences and large rearrangements in 940 Argentinian women with familial and/or personal history of breast/ovary cancer (including 230 patients without personal but with family history of cancer) and found that recurrent mutations represented only 15.08% of the total 179 mutations [39].…”
Section: Clinicomolecular Features Of Hostmentioning
confidence: 97%
“…Several recent studies have evaluated BRCA mutation in Latin American countries, and some of them have documented prevalence studies in high-risk population and in unselected invasive BC cases in Mexico (six total studies, 6.3-23.0% in high risk, 4.3% in unselected) [34][35][36], Brazil (eight studies, 3.4-22.5%, 2.3%) [37][38], Argentina (two studies, 16.2-58.3%, unknown) [33,39], Colombia (five studies, 14.3-24.5%, 1.2-4.5%) [40][41], Chile (two studies, 7.1-20.4%, unknown) [42], Costa Rica (one study, 4.5%, unknown) [43], Cuba (one study, 2.6%, unknown) [44], Peru (one study, 4.9%, unknown) [45], Uruguay (one study, 17%, unknown) [46], Venezuela (one study,17.2%, unknown) [47], Trinidad and Tobago (one study, unknown, 10.4%) [48] and The Bahamas (one study, 27.1%, unknown) [49]. Most Latin American studies identified a higher rate of BRCA1 than BRCA2 mutations [37], however studies from Costa Rica [43], Cuba [50], Puerto Rico [51] and Uruguay [46] reported the opposite finding.…”
Section: Clinicomolecular Features Of Hostmentioning
confidence: 99%
“…Identifying the prevalence of mutations in BRCA1 and BRCA2 genes in patients with breast cancer had not been performed in Peru until 2014, when Abugattas et al [28] reported the first study there. The study included 266 women, not selected by age or family history, in which the panel of 115 Hispanic's mutations (Hispanel) in BRCA1/2 genes was analyzed.…”
Section: Perumentioning
confidence: 99%